Dwifungsi Dokumen Injil Markus: Analisis Materi Historografi Injil Markus - Marlin, John (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
In The Gospel of Mark, as the earliest theological historiographical document, presents significant interpretive complexities in New Testament studies. The absence of explicit statements regarding its authorial purpose has given rise to diverse hermeneutical approaches, ranging from christological to normative-canonical interpretations. This research aims to analyze the dual function of the Gospel of Mark through a historical-critical approach to identify ecclesiological and apologetic dimensions within the context of the first-century church. The study employs descriptive-qualitative analytical methods with a historical-critical approach to the text of the Gospel of Mark. Data were collected through systematic literature review of primary and secondary sources, analysis of historical background, and comparative examination of contemporary New Testament literature. The analysis reveals that the Gospel of Mark possesses a strategic dual function: (1) as an ecclesiological document that serves to construct the identity of the early Christian community, and (2) as an apologetic document that responds to Roman persecution and political accusations against the church. The narrative structure and material selection in the Gospel of Mark reflect systematic efforts to present the Christian community as a peace-bearing group while simultaneously legitimizing the church's existence within the Roman socio-political context. The Gospel of Mark is not limited to merely kerygmatic or catechetical functions, but rather possesses significant apologetic dimensions in responding to external challenges facing the first-century church. This dual function demonstrates theological and strategic sophistication in efforts to defend and strengthen the position of the early Christian community amid political and social pressures.